2007
DOI: 10.1021/cg0608054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Symmetry on Growth-Induced Properties

Abstract: The influence of surface symmetries on growth-induced physical properties is studied. Three processes for which this impact is particularly significant are reviewed:  (i) adsorption of chiral molecules on solid substrates, (ii) symmetry reduction due to adsorption of impurities during growth, and (iii) self-poisoning during growth. It is shown that surface symmetries may propagate to the entire growth sector, leading in case of (ii) and (iii) to a crystal composed of domains with different chemical composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…The occurrence of reduction in symmetry has also been recorded in centrosymmetric crystals displaying atomic or molecular disorder. Thus for example, Gervais and Hulliger16 have demonstrated that p ‐nitro‐ p ′‐chloro‐stilbene, which crystallizes in point group 2/ m , was demonstrated to form enantiomorphous sectors, as a result of disorder, where the Cl and the NO 2 groups interchange in certain sectors of the crystal such that they convert the centrosymmetric crystal into a conglomerate of polar sectors. The reduction in symmetry in some of the sectors of this centrosymmetric crystal has been determined also by the display of pyroelectric effect in certain directions of the sector.…”
Section: “Mirror‐symmetry Breaking” With Organic Centrosymmetric Cmentioning
confidence: 99%
“…The occurrence of reduction in symmetry has also been recorded in centrosymmetric crystals displaying atomic or molecular disorder. Thus for example, Gervais and Hulliger16 have demonstrated that p ‐nitro‐ p ′‐chloro‐stilbene, which crystallizes in point group 2/ m , was demonstrated to form enantiomorphous sectors, as a result of disorder, where the Cl and the NO 2 groups interchange in certain sectors of the crystal such that they convert the centrosymmetric crystal into a conglomerate of polar sectors. The reduction in symmetry in some of the sectors of this centrosymmetric crystal has been determined also by the display of pyroelectric effect in certain directions of the sector.…”
Section: “Mirror‐symmetry Breaking” With Organic Centrosymmetric Cmentioning
confidence: 99%
“…Considering real crystal structures, e.g., nucleation processes leading to n/m (n = 2, 3, 4, 6) point groups and growth along the axis n, the stochastic process transforms pro-chiral faces into chiral sectors. Because of the mirror plane m passing through a seed, sectors involving the +n or the −n direction show an enantiomorphic relation (for a discussion of other point groups and low index faces, see [22]). …”
Section: Symmetry and Conservationmentioning
confidence: 99%
“…Neumann's principle gives thought to physical properties of bulk crystals [2], although building blocks undergo attachment to surfaces confined to 2D point groups. For growth induced properties, Neumann's principle may thus be restated as follows [3]: The symmetry elements of a physical property of a growth sector include all symmetry elements of the point group of the growth sector. Properties resulting explicitly from processes at the crystal-nutrient interface are those, which in principle should disappear if thermalization of the bulk structure far off the surface has reached the minimum of free energy.…”
mentioning
confidence: 99%
“…Explicitly, a symmetry analysis for a vector property, i.e. pyroelectricity was performed [3].Here, we shall understand dissymetrization as a constructive phenomenon for physical property formation. Vector property formation is particularly interesting in the case of molecular crystals, constituted by prolate shaped dipolar molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation